Investigating the level of awareness and the observation the charter of patient rights from the perspective of patients and nurses in Iran: a systematic review - Badri Turki; Forough Faroughi; Ali Azizi; Iman Taghizadeh Firozjaie (فصلنامه ابن سینا)
Background and aims: One of the duties of nurses is to observe the patients’ rights, which are the expectations that patients have from medical services. The aim of this study was to review previous studies about the level of awareness and observation the patient rights from the perspective of patients and nurses. Methods: In a review study the inclusion criteria of the articles were the relationship of the articles with the patient’s bill of rights, using keywords such as “Patient’s rights”, “Patient’s bill/charter of right”, “Attitude”, “Awareness”, “Nurse”, and “Iran” in the title of the article, and conducting a study specifically on nurses and patients hospitalized in the period of 1998 to 2018 in internal and external databases including SID, Iran medex, Magiran, Irandoc, pubmed, and Google scholar search engine. Results: The results showed that the observation of patients’ rights by nurses was not at a desired level. In some studies, better patient's rights were respected in nurses with more work experience or in patients with higher educational level. Conclusion: Based on the results, medical service providers should have excellent level of respect for patients’ rights with providing information to patients and their right to choose and to make decisions, because more awareness and more respect for patients' rights will lead to an increase in the quality of care and an improvement in the relations between the patient and the treatment staff as well as a decrease in the number of  patients' complaints.